Russian Trial ALGORITHM: Implementation of Combined Antihypertensive and Hypolipidemic Treatment for Clinical Efficacy Achievement in Routine Clinical Practice - D. A. Napalkov (Рациональная фармакотерапия в кардиологии)
Aim. To study the clinical outcomes (achievement of target blood pressure [BP]) and tolerability of antihypertensive and hypolipidemic therapy with fixed combinations of indapamide/perindopril, amlodipine/perindopril, amlodipine/indapamide/perindopril and rosuvastatin in patients with hypertension and high/very high cardiovascular risk in real clinical practice.Material and methods. The study included 16,788 patients from 104 cities of the Russian Federation. The duration of observation was 12 weeks. All patients had three monitoring visits. BP level was measured twice during the visits: the arithmetic mean of the obtained parameters was calculated. The results of the study were analyzed and presented by descriptive statistics.Results. The average age of the patients was 60.6±10.2 years; 42.2% of the patients were men and 57.8% women. Patients who demonstrated systolicdiastolic hypertension (BP>140/90 mm Hg) at the initial visit accounted for 73.9% (n=12,413) of the total number of participants. The average level of systolic BP at the inclusion into the study was 162.94±13.07 mm Hg, the level of diastolic BP was 93.43±8.61 mm Hg. As expected, the Russian population consists of over 90% of patients with very high (57%; n=9,586) and high (35.9%; n=6,022) additional cardiovascular risk. Despite the fact that the overwhelming majority of patients with hypertension had a high and very high additional risk, more than a third of patients received monotherapy to control their BP level (36.8%; n=6,182), while 13.8% of patients (n=2,321) had never received antihypertensive therapy before. According to the results of therapy with combination drugs based on perindopril, 92.7% of patients managed to reach the target BP levels of <140/90 mm Hg. After treatment the average level of systolic BP decreased from 162.94±13.07 mm Hg to 127.80±7.56 mm Hg, and the level of diastolic BP – from 93.43±8.61 mm Hg to 78.54±5.59. Adherence to the treatment in more than 97% of cases was recognized as very high and high. Only 10 adverse events were recorded on a large sample of patients during 12 weeks of treatment.Conclusion. In the Russian population, 73.9% of patients with hypertension and high/very high risk do not achieve the target BP levels. Application of combined therapy based on fixed combinations with perindopril allows achieving effective BP control in 93% of patients with hypertension having high and very high risk during 12 weeks with good tolerability of treatment.